Dietary exposure to short- and medium-chain chlorinated paraffins in meat and meat products from 20 provinces of China. (February 2018) - Huang, Huiting; Gao, Lirong; Zheng, Minghui; Li, Jingguang; Zhang, Lei; Wu, Yongning; Wang, Runhua; Xia, Dan; Qiao, Lin; Cui, Lili; Su, Guijin; Liu, Wenbin; et al.
Abstract: Food intake is one of the main pathways of human exposure to chlorinated paraffins (CPs). This study assessed the dietary exposure for the general Chinese population to short-chain chlorinated paraffin (SCCPs) and medium-chain chlorinated paraffins (MCCPs) through meat and meat products. Twenty samples of meat and meat products from 20 Chinese provinces were collected in 2011. As the sampling sites covered about two-thirds of the Chinese population, the meat samples were considered to be representative of the true characteristics of CPs contamination in Chinese meat products. The concentrations of SCCPs and MCCPs in the meat samples were measured using the comprehensive two-dimensional gas chromatography electron capture negative ionization high-resolution time-of-flight mass spectrometry method. Forty-eight SCCP and MCCP homolog groups were detected in the meat samples. The mean SCCP and MCCP concentrations in all meat samples were 129 ± 4.1 ng g −1 wet weight and 5.7 ± 0.59 ng g −1 wet weight, respectively. The concentrations of SCCPs and MCCPs varied in samples from different provinces. The geographical distribution of CP concentrations was similar to the distribution of CPs manufacturing plants in China. The most abundant groups of SCCPs in all samples were C10-11 Cl6-7, and the most abundant groups of MCCPs in most samples were C14 Cl7-8 . The possible sources of SCCPs and MCCPs in meat and meat products might be CP-42 and CP-52. The 50th percentile estimated daily intakes of SCCPs and MCCPs through meat consumption for a "standard" Chinese adult male were 0.13 and 0.0047 μg kg −1 bw d −1, respectively, both much lower than the tolerable daily intakes (TDIs) for SCCPs and MCCPs. This preliminary risk assessment has indicated that the indirect exposure of SCCPs and MCCPs through meat consumption does not pose significant risk to human health in China. Graphical abstract: Image 1 Highlights: SCCPs and MCCPs in meat samples from 20 Chinese provinces have been determined. The levels of SCCPs and MCCPs were higher than in Japanese samples. The concentrations of SCCPs and MCCPs in meat from different provinces varied. There was no significant risk to human health at the current intakes of SCCPs and MCCPs through consuming meat in China. Abstract : The levels of SCCPs and MCCPs in meat and meat product samples from 20 Chinese provinces were investigated as a preliminary assessment of their risk to the health of the general population.